Tariff Liberalization and Trade Integration of Emerging Countries - Anne-Célia Disdier; Lionel Gérard Fontagné; Mondher Mimouni (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate how tariff liberalization has affected exporting in emerging countries. We use a highly disaggregated bilateral measure of market access to compare tariffs applied in 1996 and 2006, which includes the timing of the Uruguay Round and episodes of bilateral liberalization. Our econometric estimations show that the reduced tariffs imposed on emerging countries have contributed to growth in their exports of differentiated goods at the intensive margin; they have not affected the probability of recording new flows. Growth in emerging countries' exports at the extensive margin of trade has been due mainly to an upward shift in their comparative advantage and improvements to their infrastructure.
Keywords: F13; F15; 330; tariffs; trade liberalization; emerging countries; margins of trade